Ananta Samakhom Throne Hall’s decorative patterns and Influences from Western Architecture - Wichaikul, Onuma (DEC Journal : Art and Design, 2022)
This article aims to study the architectural structure of Ananta Samakhom Throne Hall and Western Architecture during the 18th-19th centuries. The purpose is to compare the relationship between decorative patterns and their composition of figures. In 1908, Ananta Samakhom Throne Hall was founded by King Chulalongkorn during the historical art period of Eclecticism. This art era is distinguished in reviving the aesthetics of Greek and Roman to convey in a contemporary aspect. The architect had embraced the influences of 1) Eclecticism in the traditional process and material and 2) Neo-baroque in resuming luxury scent and element to portray through the construction of Ananta Samakhom Throne Hall. The study of this decoration shows that the architectural construction of Ananta Samakhom Throne Hall contains the composition and discipline of decorative patterns and the application of similar practices by which influenced by the West. Nevertheless, the architect could bend the design according to Thai tradition and accommodation.